Hydrothermal synthesis of nanocrystalline hydroxyapatite-graphene nanosheet on Ti-6Al-7Nb: mechanical and in vitro corrosion performance - Yigit, Oktay; Dikici, Burak; Ozdemir, Niyazi (Springer, 2021)
The hybrid coatings containing the graphene nano-sheet (GNS) and nano-hydroxyapatite (nHA) phases have been successfully synthesized on Ti6Al7Nb alloys by a one-step hydrothermal method. The hydrothermal reaction was carried out for 24h at 200 degrees C. The GNS ratio has been altered as 1, 3, 5 and 7wt.% in the coatings and, the results have compared with non- GNS containing coatings. The effect of the GNS ratio on the microstructure, hardness, and in vitro corrosion responses has been investigated in detail. The characterizations of the coatings were carried out by SEM, EDS, AFM, XRD and, FTIR. The corrosion behavior of the hybrid coatings was compared in Kokubo's solution at 37 degrees C by using potentiodynamic polarization tests. The results showed that the hydroxyapatite phases were deposed on the graphene layers with nano-size nucleation with its Ca/P stoichiometric ratio. The best hydrophilicity (similar to 52 degrees) property has been obtained in nHA/3GNS coatings. In addition, the corrosion rates of coatings increased in the following order: nHA/3GNS
Keywords: Titanium-Alloys; Coatings; Composite; Deposition; Resistance; Oxidation; Fabrication; Morphology